Diversity of Maize Shoot Apical Meristem Architecture and Its Relationship to Plant Morphology. Issue 5 (1st May 2015) - Thompson, Addie M; Yu, Jianming; Timmermans, Marja C P; Schnable, Patrick; Crants, James E; Scanlon, Michael J; Muehlbauer, Gary J
Abstract: The shoot apical meristem contains a pool of undifferentiated stem cells and controls initiation of all aerial plant organs. In maize ( Zea mays ), leaves are formed throughout vegetative development; on transition to floral development, the shoot meristem forms the tassel. Due to the regulated balance between stem cell maintenance and organogenesis, the structure and morphology of the shoot meristem are constrained during vegetative development. Previous work identified loci controlling meristem architecture in a recombinant inbred line population. The study presented here expanded on this by investigating shoot apical meristem morphology across a diverse set of maize inbred lines. Crosses of these lines to common parents showed varying phenotypic expression in the F1, with some form of heterosis occasionally observed. An investigation of meristematic growth throughout vegetative development in diverse lines linked the timing of reproductive transition to flowering time. Phenotypic correlations of meristem morphology with adult plant traits showed an association between the meristem and flowering time, leaf shape, and yield traits, revealing links between the control and architecture of undifferentiated and differentiated plant organs. Finally, quantitative trait loci mapping was utilized to map the genetic architecture of these meristem traits in two divergent populations. Control of meristem architecture was mainly population-specific, with 15 total unique loci mapped across the two populations with only one locus identified in both populations.